Towards Smart World Homes to Cities Using Internet of Things - Sharma, Lavanya (Boca Raton : Chapman & Hall/CRC, 2020)
Towards Smart World: Homes to Cities Using Internet of Things provides an overview of basic concepts from the rising of machines and communication to IoT for making cities smart, real-time applications domains, related technologies, and their possible solutions for handling relevant challenges. This book highlights the utilization of IoT for making cities smart and its underlying technologies in real-time application areas such as emergency departments, intelligent traffic systems, indoor and outdoor securities, automotive industries, environmental monitoring, business entrepreneurship, facial recognition, and motion-based object detection. Features The book covers the challenging issues related to sensors, detection, and tracking of moving objects, and solutions to handle relevant challenges. It contains the most recent research analysis in the domain of communications, signal processing, and computing sciences for facilitating smart homes, buildings, environmental conditions, and cities. It presents the readers with practical approaches and future direction for using IoT in smart cities and discusses how it deals with human dynamics, the ecosystem, and social objects and their relation. It describes the latest technological advances in IoT and visual surveillance with their implementations. This book is an ideal resource for IT professionals, researchers, undergraduate or postgraduate students, practitioners, and technology developers who are interested in gaining deeper knowledge and implementing IoT for smart cities, real-time applications areas, and technologies, and a possible set of solutions to handle relevant challenges. Dr. Lavanya Sharma is an Assistant Professor in the Amity Institute of Information Technology at Amity University UP, Noida, India. She has been a recipient of several prestigious awards during her academic career. She is an active nationally recognized researcher who has published numerous papers in her field.
15. Diagnostic of the Malarial Parasite in RBC Images for Automated Diseases Prediction -- 16. Design of a Multipurpose Android-Controlled Robotic Arm for a Smart City -- 17. From Moving Objects Detection to Classification and Recognition: A Review for Smart Environments -- 18. Human Detection and Tracking Using Background Subtraction in Visual Surveillance -- 19. The Future of Smart Cities -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; Smart cities; COMPUTERS / Database Management / Data Mining; COMPUTERS / Computer Science